Wioski tematyczne w powiecie tucholskim = Theme villages in powiat tucholski - Kawska, Paulina; Gotowski, Rafal (Journal of Education, Health and Sport, 2017)
Kawska Paulina, Gotowski Rafał. Wioski tematyczne w powiecie tucholskim = Theme villages in powiat tucholski. Journal of Education, Health and Sport. 2016;6(11):46-53. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.163526 http://ojs.ukw.edu.pl/index.php/johs/article/view/3960 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 12.10.2016. Accepted: 27.10.2016. Wioski tematyczne w powiecie tucholskim Theme villages in powiat tucholski Paulina Kawska, Rafał Gotowski Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska Słowa kluczowe: wioska tematyczna, odnowa wsi, specjalizacja. Key words: theme village, village renewal, specialization. Streszczenie Artykuł koncentruje się na zagadnieniu wiosek tematycznych funkcjonujących w świadomości mieszkańców powiatu tucholskiego, a w szczególności z kojarzeniem terminu wioska tematyczna i wiedzy badanych osób o wioskach tego typu. Badania pokazały również stopień wypromowania produktu turystycznego jakim są wioski tematyczne wśród mieszkańców powiatu tucholskiego oraz ocenę ich atrakcyjności. Abstract The article presents the issue of the theme villages by referring them to the awareness of the Powiat Tucholski residents connected with the villagesexisting in its area. That is why it was decided to conduct a survey. At the verybeginning, the respondents were asked what they associate the term theme village with, further questions were focused on the inhabitant’s knowledge of the set up in the research areavillages. The survey was supposed to show how much the tourist product - theme villages created by the local societies has been promoted among the Powiat Tucholski residents and how attractive it is for them.